Pregnancy Outcomes in Women with 1-Hour Glucose Challenge Test ≥ 200 mg/dL - Ankumah, Nana-Ama; Tita, Alan T. N.; Biggio, Joseph R.; Harper, Lorie M. (American Journal of Perinatology, 2016)
Objective Many protocols diagnose gestational diabetes mellitus (GDM) solely on a 1-hour glucose challenge test (GCT) ≥ 200 mg/dL. However, pregnancy outcomes in these women compared with women diagnosed with a 3-hour glucose tolerance test (GTT) has not been adequately evaluated. We hypothesize that a 1-hour GCT ≥ 200 mg/dL is associated with worse pregnancy outcomes as compared with a GCT 135 to 199 mg/dL with positive GTT.Study Design A retrospective cohort of singleton pregnancies complicated by GDM. Maternal outcomes included A2DM, preeclampsia, primary cesarean, and failed trial of labor after cesarean. Perinatal outcomes were large/small for gestational age, shoulder dystocia, and birth injury. Groups were compared with t-test and chi-square test, and logistic regression to adjust for confounders.Results A total of 602 women diagnosed with GDM by 1-hour GCT 135 to 199 mg/dL and confirmatory 3-hour GTT (< 200 group) and 225 women diagnosed with 1-hour GCT ≥ 200 alone (≥ 200) were included. The ≥ 200 group had a higher incidence of preeclampsia (16.4 vs. 10.6%) and shoulder dystocia (3.1 vs. 1.0%). Adjusted odds ratio and 95% confidence interval were 1.80 (1.10–2.94) and 5.10 (1.25–20.76), respectively.Conclusion Preeclampsia and shoulder dystocia are more frequent in women with GCT ≥ 200 mg/dL than those with a positive GTT following a GCT of 135 to 199 mg/dL.
Keywords: gestational diabetes; shoulder dystocia; preeclampsia; birth injury